1989
DOI: 10.1177/036354658901700502
|View full text |Cite
|
Sign up to set email alerts
|

The results of conservative management of juvenile osteochondritis dissecans using joint scintigraphy

Abstract: A prospective clinical study used joint scintigraphy to investigate conservative treatment of juvenile osteochondritis dissecans (JOCD) of the femoral condyle. The predictive value of scintigraphic evaluation and various parameters (age at onset, sex, location and size of lesion) were analyzed. Over a 10 year period, the senior author followed 92 knees in 76 patients, 60 of whom were male and 16 female (11 and 5 bilaterals, respectively). All patients were participants in athletics or exercise programs. All pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
159
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 199 publications
(169 citation statements)
references
References 17 publications
8
159
0
2
Order By: Relevance
“…This provides visual access to the common locations for OCD lesions. Furthermore, since Cahill et al [11,23] demonstrated 16 of 76 patients had bilateral knee involvement, we believe it clinically acceptable to obtain contralateral films to evaluate for bilateral involvement.…”
Section: Imagingmentioning
confidence: 95%
See 2 more Smart Citations
“…This provides visual access to the common locations for OCD lesions. Furthermore, since Cahill et al [11,23] demonstrated 16 of 76 patients had bilateral knee involvement, we believe it clinically acceptable to obtain contralateral films to evaluate for bilateral involvement.…”
Section: Imagingmentioning
confidence: 95%
“…After plain film radiology, some authors have recommended the next evaluation should be scintigraphy because it provided information regarding blood flow to the lesion [8,11,50,65]. However, it fails to provide detailed information about the state of affairs concerning the articular cartilage.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[8][9][10][11] While no defined mechanism of failure following fixation has been identified, we suspect that subjecting the repair site to loads in shear is a contributing factor. Our results revealed all methods of internal fixation performed significantly better than the control, with the construct using the longest AO screw and threaded washer providing the greatest stability.…”
Section: Discussionmentioning
confidence: 99%
“…A 4-month trial of protected weightbearing is recommended in this group. 3,[8][9][10][11][12] Surgical treatment is reserved for the patient with JOCD that has failed conservative measures and for those who are skeletally mature at the time of presentation. A variety of fixation methods have been used successfully in achieving fracture healing, including Kirschner wire (K-wire) fixation, 3,9 cannulated screws, 10 Herbert screws, 13 compression screws, 14 biodegradable rods, 15 biologic fixation with autogenous osteochondral plugs, 16 and nonabsorbable sutures.…”
Section: Introductionmentioning
confidence: 99%